If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 5)(4x + -2) = (2x)(4x) Reorder the terms: (5 + 2x)(4x + -2) = (2x)(4x) Reorder the terms: (5 + 2x)(-2 + 4x) = (2x)(4x) Multiply (5 + 2x) * (-2 + 4x) (5(-2 + 4x) + 2x * (-2 + 4x)) = (2x)(4x) ((-2 * 5 + 4x * 5) + 2x * (-2 + 4x)) = (2x)(4x) ((-10 + 20x) + 2x * (-2 + 4x)) = (2x)(4x) (-10 + 20x + (-2 * 2x + 4x * 2x)) = (2x)(4x) (-10 + 20x + (-4x + 8x2)) = (2x)(4x) Combine like terms: 20x + -4x = 16x (-10 + 16x + 8x2) = (2x)(4x) Remove parenthesis around (2x) -10 + 16x + 8x2 = 2x(4x) Remove parenthesis around (4x) -10 + 16x + 8x2 = 2x * 4x Reorder the terms for easier multiplication: -10 + 16x + 8x2 = 2 * 4x * x Multiply 2 * 4 -10 + 16x + 8x2 = 8x * x Multiply x * x -10 + 16x + 8x2 = 8x2 Add '-8x2' to each side of the equation. -10 + 16x + 8x2 + -8x2 = 8x2 + -8x2 Combine like terms: 8x2 + -8x2 = 0 -10 + 16x + 0 = 8x2 + -8x2 -10 + 16x = 8x2 + -8x2 Combine like terms: 8x2 + -8x2 = 0 -10 + 16x = 0 Solving -10 + 16x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 16x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 16x = 0 + 10 16x = 0 + 10 Combine like terms: 0 + 10 = 10 16x = 10 Divide each side by '16'. x = 0.625 Simplifying x = 0.625
| (2x+5)(4x-2)=(2x)(4x)+(2x)(-2)+(5)(4x)+(5)(-2) | | -15x^2+11x-2=0 | | 12x^2+13x-30=0 | | 6x^2-11x+2=0 | | ln(x)-ln(x-7)=ln(2) | | ln(x)-ln(x-7)=ln(2) | | 30r^2-13r-3=0 | | 30t^2-49t+20=0 | | 589270957349857476-4= | | 12x^2+5-23x=0 | | 3(4x+5)=63 | | 5x^2-6x+4=0 | | 3a+8=20 | | 2a+9=17 | | a+1=4 | | X(3)=12 | | 16x-8y=64 | | 4(3q+7)=7 | | 7x+38=-4 | | 11(16-g)=22 | | f=-2f-9 | | -84-8x=9x+18 | | 156-7x=29x+24 | | 145-6x=3x+10 | | 8f=-2f-10 | | 9x=125 | | 2a+12=6 | | 7x=-64 | | 7x+32=-32 | | x=5000 | | a+6=4 | | x=2100 |